Research on the deflection of metal bar with V-shaped notch in low-stress cropping process. (August 2021) - Yang, Ning; Tao, Jishao; Fu, Shulin; Yang, Bohan; Wang, Hang; Guo, Weijian; Xu, Jiayi; Zhang, Lijun
Graphical abstract: Aiming at the metal bar with V-shaped notch in low-stress cropping, the deflection construction method of "five-segment type" discontinuous variable cross-section bar model based on strain energy method is proposed. The characterization formula of deflection suitable for the low-stress cropping process is established theoretically and verified by experimental study. On this basis, the law θ i of follow-up rotation angle of loading die is analyzed, and the effective method to apply desirable loads is obtained. The evaluation parameter ω i ( L B / 2 R 0 ) of allowable value of deflection is proposed, and the allowable deflection range ω 1, ω 2 = 0.02343mm, 0.15383mm of 45# steel bar with a diameter of 15mm is obtained, which can be applied to low-stress cropping and meet the requirements of industrialization. Highlights: The deflection construction method of "five-segment type" bar model is proposed. The formula of deflection suitable for low-stress cropping process is established. The follow-up steering law and effective method to apply desirable load are obtained. Put forward the allowable value of deflection suitable for low-stress cropping. Abstract: In view of the deflection of metal bars in low-stress cropping process, which leads to serious extrusion damage on the surface of bar and difficulty to apply loads effectively, a "five-segment type" discontinuous variable cross-section bar model is established in this paper. The strain energy method is developed to establish the influence of V-shaped notch parameters on the deflection, and its accuracy is elevated with XFEM method, which is used to quantify the influence of crack depth. Finally, the characterization formula of deflection in the low-stress cropping process is established theoretically. The dynamic and static strain-deflection test and analysis platform is built on the low-stress cropping machine. The experimental results of 45# steel bar confirm the validity of the formula. On this basis, the law θ i of follow-up rotation angle of loading die is analyzed, and the effective method to apply desirable loads is obtained. The evaluation parameter ω i ( L B / 2 R 0 ) of allowable value of deflection at crack initiation is proposed, and the allowable deflection range ω 1, ω 2 = 0.02343mm, 0.15383mm of 45# steel bar with a diameter of 15 mm is given, which can be applied to low-stress cropping and meet the requirements of industrialization.